Integrated Proteomics and Metabolomics Analysis in Pregnant Rat Hippocampus After Circadian Rhythm Inversion - Lin, Jingjing; Sun, Xinyue; Dai, Xiaofeng; Zhang, Shaoying; Zhang, Xueling; Wang, Qiaosong; Zheng, Qirong; Huang, Minfang; He, Yuanyuan; Lin, Rongjin (Frontiers in Physiology, 2022)
To investigate the changes in proteins, metabolites, and related mechanisms in the hypothalamus of pregnant rats after circadian rhythm inversion during the whole pregnancy cycle. Twelve Wistar female rats aged seven weeks were randomly divided into control (six rats) and experimental (six rats) groups at the beginning of pregnancy. The control group followed a 12 h light-dark cycle (6 am to 6 pm light, 6 pm to 6 am dark the next day), and the experimental group followed a completely inverted circadian rhythm (6 pm to 6 am light the next day, 6 am to 6 pm dark). Postpartum data were collected until 7 to 24 hours after delivery, and hypothalamus samples were collected in two groups for quantitative proteomic and metabolism analysis. The differential proteins and metabolites of the two groups were screened by univariate combined with multivariate statistical analysis, and the differential proteins and metabolites enriched pathways were annotated with relevant databases to analyze the potential mechanisms after circadian rhythm inversion. A comparison of postpartum data showed that circadian rhythm inversion can affect the number of offspring and the average weight of offspring in pregnant rats. Compared with the control group, the expression of 20 proteins and 37 metabolites was significantly changed in the experimental group. The integrated analysis between proteins and metabolites found that RGD1562758 and lysophosphatidylcholine acyltransferase 1 (LPCAT1) proteins were closely associated with carbon metabolism (Choline, NAD+, L-Glutamine, Theobromine, D-Frutose, and Pyrucate) and glycerophospholipid metabolism (Choline, NAD+, L-Glutamine, Phosphatidylcholine, Theobromine, D-Frutose, Pyrucate and Arachidonate). Moreover, the Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that the differential metabolites enriched in Adenosine-Triphosphate (ATP)-binding cassette (ABC) transporters. Our study suggested that circadian rhythm inversion in pregnant rats may affect the numbers, the average weight of offspring, and the expressions of proteins and metabolism in the hypothalamus, which may provide a comprehensive overview of the molecular profile of circadian rhythm inversion in pregnant groups.